Patient Access Rights to Medical Records Comparative Study Indonesian-Malaysian Law - Komala, Vira; Setiadi, Edi; Ratna Suminar, Sri (Greenation International Journal of Law and Social Sciences, 2024)
Article 297 paragraph (2) of Law Number 17 of 2023 concerning Health explains that every patient has the right to access the information contained in medical record documents. The regulation of patient access rights to medical records in Indonesia has given rise to various interpretations. The public has interpreted the meaning of the patient's right of access to information in medical record documents for themselves. This is where the problem arises, hospitals often face patients for some reason requiring medical records. With access rights, patients can freely use the contents of medical records as they wish. Seeing these conditions, the author wants to compare Malaysia's approach to regulating patient access rights to medical records. Objective: to examine the legal position and gaps using a comparative analysis of patient access to medical records in Indonesia and Malaysia. The research method uses normative juridical data with secondary data and is analyzed using descriptive analysis.